2014
DOI: 10.5539/ass.v10n6p205
|View full text |Cite
|
Sign up to set email alerts
|

Risk Attitude towards Mandatory Retirement Protection in Hong Kong: Why Are Risky Investments More Attractive?

Abstract: The government of Hong Kong Special Administrative Region (HKSAR) launched the Mandatory Provident Fund (MPF) scheme as a major source of retirement protection. Now, over 2.6 million employees and self-employed persons are currently making contribution to this scheme and they are required to decide on allocation of their MPF contributions to different MPF choices. However, we know little about how their decisions are formed. One major contribution of this study is to investigate people's perceptions of MPF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In the context of financial decision-making, a large body of research has shown that people's risk attitude affects their financial portfolios and activeness in trading (Barasinska et al, 2012;Fellner & Maciejovsky, 2007;Weber & Milliman, 1997;Wong, 2014). For example, a survey in Germany showed that risk-averse private investors tend to hold risk-free assets in their investment portfolios (Barasinska et al, 2012).…”
Section: Mpf or Isa Choices And Individual Risk Attitudementioning
confidence: 99%
See 2 more Smart Citations
“…In the context of financial decision-making, a large body of research has shown that people's risk attitude affects their financial portfolios and activeness in trading (Barasinska et al, 2012;Fellner & Maciejovsky, 2007;Weber & Milliman, 1997;Wong, 2014). For example, a survey in Germany showed that risk-averse private investors tend to hold risk-free assets in their investment portfolios (Barasinska et al, 2012).…”
Section: Mpf or Isa Choices And Individual Risk Attitudementioning
confidence: 99%
“…Different MPF or ISA choices involve different levels of risk (Wong, 2014). Take the MPF market as an example, in which the MPF conservative fund is a less risky choice than an equity fund.…”
Section: Mpf or Isa Choices And Individual Risk Attitudementioning
confidence: 99%
See 1 more Smart Citation